ANALISIS KESIAPAN PESERTA DIDIK PADA ASESMEN KOMPETENSI MINIMUM DI SEKOLAH DASAR - Dwi Ariyanti, Mei Riska; Ida Dwijayanti; Sumarno (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The Minimum Competency Assessment is an assessment of the fundamental competencies required by all students to develop their own capacity and participate actively in society. The competency domain in AKM is structured around three abilities, namely determining, understanding and reflecting, with questions presented in the form of multiple choice, complex multiple choice, matching, short essay and description. There are two basic competencies measured in the AKM program, namely reading literacy and mathematics literacy ( numeracy). The aim of this research is to see how prepared students are for the minimum competency assessment (AKM) in elementary schools. The type of research used is qualitative research. The research instruments are in the form of questionnaires and interviews. The results of the research showed that 61 students (54.5%) strongly agreed with the readiness for the minimum competency assessment of 112 students in elementary schools. Furthermore, 40 students (35.7%) agreed. And regarding readiness in solving questions, 28 students (25%) strongly agreed. Furthermore, 82 students (73.2%) agreed. So based on the data above, it can be understood that students' readiness for the minimum competency assessment in elementary schools is classified as Very Ready Keywords: AKM, Literacy, Numeracy, Readiness